CAMPUR KODE BAHASA JAWA BANYUMASAN DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH MENENGAH KEJURUAN - Bekty Tandaningtyas Sundoro; Sarwiji Suwandi; Budhi Setiawan (Universitas Negeri Makassar, 2018)
Code-Mixing Javanese Language of Banyumasan in Indonesian Language Learning at Vocational High School. This research will describe: (1) the form of code mixing, and (2) the factor that causing of code mixing that occur in the process of Indonesian learning class. Data and data sources in this research are a written data about speech that appear in a process of Indonesian language learning. Validity data technique is use triangulation of data source and informant review. Data analysis used intralingual method. The results of this study found the use of code mixing in Indonesian learning class in The Country Vocational High School of Banyumas. The form of code mixing that found are namely: (1) word insertion, (2) phrase insertion, (3) clause insertion, (4) the word repetition, and (5) idiom. The factor that causing of code mixing are: (1) changing situation, (2) want to explain something, and (3) establishing intimacy between teacher and student.